2009
DOI: 10.1002/aic.11994
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characterization of static mixers. The S‐shaped micromixer as a case study

Abstract: We investigate the steady-state performance of a planar micromixer composed of several S-shaped units. Mixing efficiency is quantified by the decay of the scalar variance downstream the device for generic feeding conditions. We discuss how this decay is controlled by the spectral properties of the advection-diffusion Floquet operator, F, that maps a generic scalar profile at the inlet of a single unit into the corresponding profile at the unit outlet section. Two advantages characterize the Floquet operator ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Therefore, a passive micromixer is utilized in our design. The typical passive methods employed to enhance mixing efficiency predominantly rely on chaotic convection effects by handling flows within the microchannels or by improving diffusion via (1) increasing the contact area and/or time among mixing species [20], or via (2) influencing the flow streamlines to enhance dispersion-caused mass transfer [21][22][23]. Taking the microscale fluid characteristics and mixing performance into account, three specified microchannel structures were studied and compared by numerical simulation using Ansys Fluent software to select the most suitable one for the fabrication of a microfluidic chip for exosomes isolation.…”
Section: Micromixer Designmentioning
confidence: 99%
“…Therefore, a passive micromixer is utilized in our design. The typical passive methods employed to enhance mixing efficiency predominantly rely on chaotic convection effects by handling flows within the microchannels or by improving diffusion via (1) increasing the contact area and/or time among mixing species [20], or via (2) influencing the flow streamlines to enhance dispersion-caused mass transfer [21][22][23]. Taking the microscale fluid characteristics and mixing performance into account, three specified microchannel structures were studied and compared by numerical simulation using Ansys Fluent software to select the most suitable one for the fabrication of a microfluidic chip for exosomes isolation.…”
Section: Micromixer Designmentioning
confidence: 99%
“…In single-phase mixtures, that is, when the suspended species are molecules and can be considered as point-sized, the interaction between convective and diffusive transport is typically exploited to improve the rate of homogenization of the concentration profiles within the mixture [1]. Here, the synergistic interaction between advection and diffusion occurs via the amplification of concentration gradients by cross-sectional velocity components (e.g., triggered by complex boundary geometries [2] as well as inertial [3], electro-osmotic [4], and magnetohydrodynamic effects [5] or a combination of the above [6]), which sustain the homogenizing action of the Fickian flux as the mixture flows downstream the device. Symmetrically, the outcome of tracer mixing experiments can be used to infer properties of the velocity profiles within the microfludic channels, especially as regards the occurrence of slip boundary conditions for the flow when the characteristic dimension of the cross-section falls below the micrometric scale [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…where F T � 1 (thermal accommodation coefficient), c � 1.4, and Pr � 0.7 are assumed to be the typical values for air [26][27][28]. It can be observed that model predictions for θ b (ζ) are actually very accurate in the whole range of Peclet values Pe ∈ [10 − 2 , 10 5 ] because (1), at low Pe values, the simplifying assumption (z 2 ϕ/zζ 2 ) ≪ (d 2 θ b /dζ 2 ) holds true and (2), at high Pe values, the entire axial conduction term (z 2 θ/zζ 2 ) becomes negligible with respect to the axial convective contribution (Peα/4)v(ρ)(zθ/zζ) [38][39][40].…”
Section: Comparison With Numerical Resultsmentioning
confidence: 99%
“…In the absence of dissipation, that is, Br � 0, both Nu 0 (ζ) and Nu ∞ (ζ) become constant and independent of the wall heat flux function (see (37) and (38) for Br � 0). For this reason, the values of 〈Nu 0 〉 and 〈Nu ∞ 〉 reported in Figures 10 A-B for Br � 0 represent the asymptotic limits…”
Section: Influence Of Wall Heat Flux Function and Transport Parametermentioning
confidence: 99%